In vitro effectiveness of silicon dioxide and graphene nanoparticles combined with extracts of Bacillus amyloliquefaciens against phytopathogenic fungi - Cerna-Chávez, Ernesto; Orozco-Plancarte, Antonio; Ochoa-Fuentes, Yisa María; Landeros-Flores, Jeronimo; Jasso de Rodríguez, Diana; Hernández Pérez, Anselmo (Revista Mexicana de Ciencias Agrícolas, 2024)
The use of nanoparticles in agriculture opens the opportunity for the development of agro-products with this technology, aimed at controlling diseases caused by phytopathogenic fungi. This study aimed to evaluate in vitro the inhibitory effect of silicon dioxide (SiO2 NPs) and graphene nanoparticles (Graf NPs) mixed with extracts of Bacillus amyloliquefaciens (EcBa) on the mycelial development and formation of reproductive structures of Fusarium solani, Rhizoctonia solani, Colletotrichum acutatum, and Alternaria alternata. For the biological effectiveness test, the poisoned medium technique was used under a completely randomized design of two doses (DE70 and DE90) and absolute control with 20 replications for each treatment. Data were analyzed using an analysis of variance and Tukey’s mean test (p≤ 0.05). Effective doses were calculated using a Probit analysis. The treatment that showed the best inhibitory effect was SiO2 NPs + EcBa since it managed to inhibit mycelium growth and decreased the production of reproductive structures (spores and sclerotia) by 84% to 100% with low doses of Fusarium solani, Rhizoctonia solani, Colletotrichum acutatum, and Alternaria alternata, followed by Graf Nps + EcBa, EcBa, at higher doses, they obtained 83.7 to 100% inhibition, respectively.